Герб, флаг, гимн России - Голованова Марина Петровна (РОСМЭН, 2004)
Экземпляры: Селтинская районная библиотека (ч/з) (20170314) / Инвентарный номер: 188623 / Цена: / Авт.знак: Г 61 / ГРНТИ: 03.23 / ББК: 63.2